Long-Term Cost Performance of Corrosion-Resistant Reinforcements in Structural Concrete - Younis, Adel; Ebead, Usama (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Corrosion, which leads to the premature deterioration of reinforced concrete (RC) structures, is increasingly an issue of global concern. Accordingly, corrosion-resistant materials have emerged as alternative reinforcement solutions in concrete structures. Yet, the high initial cost of such materials may mitigate their potential use. This paper reports on the results of two life-cycle-cost-analysis (LCCA) studies that aim at verifying the long-term cost performance of corrosion-resistant reinforcements in structural concrete. The first study conducted a 100-year-based LCCA study to evaluate the relative cost savings of structural concrete that combines seawater, recycled coarse aggregates, and glass fiber-reinforced polymer (GFRP) reinforcement in high-rise buildings as compared to a traditional reinforced concrete (i.e., freshwater-mixed, natural-aggregate, black-steelreinforced). In the second study, a life-cycle-cost comparison was established among four reinforcement alternatives, viz., conventional steel, epoxy-coated steel, stainless steel, and GFRP for a RC water chlorination tank considering a 100-year study period. The results of these two studies suggest that the use of corrosion-resistant reinforcement (especially GFRP) in structural concrete may potentially lead to significant cost savings in the long term: the net present cost of GFRP-RC structures was generally 40-50% lower than that reinforced with black steel.